Advokasi Asosiasi Pesepak Bola Profesional Indonesia Sebagai Upaya Pemenuhan Hak Pemain Sepak bola Profesional di Indonesia - Polanunu, Abdul Basir Donny; Mahendra, Yusril Ihza (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2021)
Abstract—The Football industry in Indonesia is currently in the process of developing towards a more advanced football system. To achieve these goals, the stakeholders have taken few efforts such as early age football coaching, develop adequate infrastructure, and also increase the professionalism of the implementation of the competition, accompanied by the support of each club involved. These efforts have been harmonized with the standardization of the international football industry under the auspices of FIFA. However, it seems that the efforts to develop the football industry have not yet been able to realize the indicators of the modern football system as a whole. That is because there are still many cases where the rights of professional football players are neglected by stakeholders. Therefore, the existence of APPI as a form of representation of the people who are engaged in football trying to complement the strength of the football industry in Indonesia. The movement of APPI, which advocates a lot of the rights of football players, will support stakeholders in strengthening the development of the football industry in Indonesia comprehensively. The concept of civil society will be used to help the writer find the characteristics of the efforts from APPI for football in Indonesia.Keywords: advocacy, appi, indonesian football, rights of professional football Abstrak—Industri sepak bola di Indonesia saat ini berada dalam proses pengembangan menuju sistem persepakbolaan yang lebih maju. Upaya yang coba dilakukan oleh para stakeholder ialah pembinaan sepak bola usia dini, infrastruktur memadai, dan juga profesionalitas pegelaran kompetisi diiringi oleh penunjangan dari klub masing-masing yang terlibat. Hal ini tentunya sudah diselaraskan dengan standardisasi industri persepakbolaan internasional di bawah naungan FIFA. Namun tampaknya upaya pengembangan industri sepak bola yang dilakukan masih belum menjamah indikator sistem persepakbolaan modern secara keseluruhan. Hal itu dikarenakan masih banyak didapati masalah pemenuhan hak-hak pemain sepak bola profesional yang lalai ditangani oleh para pemangku kepentingan. Maka dari itu, keberadaan APPI sebagai wujud representasi dari masyarakat yang bergerak di lingkup persepakbolaan berusaha melengkapi kekuatan industri sepak bola di Indonesia. Gerakan oleh APPI yang banyak mengadvokasi hak-hak pemain sepak bola di Indonesia akan membantu para pemangku kepentingan dalam menguatkan pengembangan industri sepak bola di Indonesia secara komprehensif. Penggunaan konsep civil society akan digunakan agar membantu penulis menemukan karakteristik dari upaya yang dilakukan APPI terhadap persepakbolaan di Indonesia. Kata kunci: advokasi, appi, hak pemain sepak bola profesional, sepak bola indonesia